1993
DOI: 10.1073/pnas.90.22.10773
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing and membrane association of putative nonstructural proteins of hepatitis C virus.

Abstract: By using a plasmid-based transient protein expression system in cultured cels and an in vitro transcription/translation system, we analyzed the proteolytic processing of the putative nonstructural protein region of the precursor polyprotein from a Japanese type of hepatitis C virus. In addition to the previously reported viral proteins, p21 and p70, we identified products of 4 kDa (p4), 27 kDa (p27), 56 kDa (p56), 58 kDa (p58), and 66 kDa (p66). These products were produced in a viral serine proteinase (protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
259
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(265 citation statements)
references
References 27 publications
5
259
0
1
Order By: Relevance
“…In the absence of a satisfactory cell culture system for propagating the virus, studies of its mode of gene expression have depended upon the use of heterologous systems for protein expression, including in vitro translation, transient expression in mammalian cells and production of recombinant vaccinia viruses. By these methods, it has been established that the NS3 region of the polyprotein contains a serine proteinase domain which is responsible for cleavage of the downstream polyprotein in at least four places (Bartenschlager et al, 1993(Bartenschlager et al, , 1994Eckart et al, 1993;Grakoui et al, 1993;Hijikata et al, 1993;Tomei et al, 1993 ;Manabe et al, 1994). By analogy with the yellow fever virus (Chambers et al, 1990) this proteinase is probably essential for the production of infectious virus, and hence represents a possible target for chemotherapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a satisfactory cell culture system for propagating the virus, studies of its mode of gene expression have depended upon the use of heterologous systems for protein expression, including in vitro translation, transient expression in mammalian cells and production of recombinant vaccinia viruses. By these methods, it has been established that the NS3 region of the polyprotein contains a serine proteinase domain which is responsible for cleavage of the downstream polyprotein in at least four places (Bartenschlager et al, 1993(Bartenschlager et al, , 1994Eckart et al, 1993;Grakoui et al, 1993;Hijikata et al, 1993;Tomei et al, 1993 ;Manabe et al, 1994). By analogy with the yellow fever virus (Chambers et al, 1990) this proteinase is probably essential for the production of infectious virus, and hence represents a possible target for chemotherapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal third of the hepatitis C virus (HCV) 1 NS3 protein contains a trypsin-like serine protease that accomplishes four out of the five processing events that take place during maturation of the nonstructural portion of the HCV polyprotein, performing cleavages at the NS3-NS4A, NS4A-NS4B, NS4B-NS5A, and NS5A-NS5B junctions (1)(2)(3)(4)(5)(6). It has been shown that cleavage between NS3 and NS4A is an intramolecular event, whereas all remaining junctions are processed in trans.…”
mentioning
confidence: 99%
“…Previous studies have shown that NS4A, besides stabilizing NS3, is responsible for the localization of the NS3‐4A complex at the organelle's membranes 21, 30, 31. Tanji et al .…”
Section: Resultsmentioning
confidence: 99%